Global Advances in Value-Based Payment and Their Implications for Global Health Management Education, Development, and Practice - Counte, Michael A.; Howard, Steven W.; Chang, Larry; Aaronson, William (Frontiers in Public Health, 2019)
Global advances in health policy reform, health system improvement and health management education and practice need to be closely aligned to successfully change national health policies and improve the performance of health care delivery organizations. This paper describes the globally acknowledged need for incentive-based organizational performance and relevant implications for health care management education (HCME) and practice. It also outlines the major rationale underlying Value-Based Payment (VBP) or Pay for Performance (P4P) health policy initiatives and their basic elements. Clearly, the major global health policy shift that is underway will likely ultimately have major impacts on the strategic and operational management and performance of health care delivery organizations. Thus, practical specific suggestions are made regarding changes that need to be introduced and strengthened in contemporary health care management education and development programs to help organizational managers in the future.